Factors That Related With Diptheria Cases of Children in Bangkalan Health Centers in 2016 - Isnaniyanti Fajrin Arifin; Corrie Indria Prasasti (Universitas Airlangga, 2017)
Diphtheria cases in Bangkalan District have increased every year. In 2015, 19 cases were found in Bangkalan with a Case Fatality Rate (CFR) of 15.79% spread across 13 villages. This research was conducted to analyze the risk factors associated with cases of child diphtheria at the Public health center (PHC) of Bangkalan. This study uses a case-control study design. This research was conducted at PHC of Bangkalan in January - September 2016. Data collection used interview techniques with a questionnaire, observation, and measurement guide. The number of samples was 48 respondents with 8 cases and 40 controls. The independent variables studied were characteristics (age, sex, education level), immunization status of Diphtheria Polio Pertussis (DPT), and the physical environment, while the dependent variable is the diphtheria incident in children. Data analysis using computer computing. The results showed that the level of education (p = 0.016; OR = 1.67) and DPT immunization status (p = 0.037; OR = 4.667) were related to the incidence of diphtheria in children. It is recommended that health workers, especially village midwives in collaboration with cadres need to increase their role as educators and counselors in providing information to the community in the form of counseling to the community related to the risk of diphtheria transmission and the benefits of basic immunization to all villages until reaching the Universal Child Immunization (UCI) target.